Informal Food Markets in Quezon City and Pasay City, Philippines: A Rapid Assessment. Resilient Cities Initiative Research Report - Roa, J. (International Potato Center, 2023)
Cognizant of the centrality of food systems in a rapidly urbanizing world amidst environmental and health risks, the Resilient Cities Initiative will strengthen capacities for research and innovation in the management of urban food systems in Africa, Asia, and Latin America. As part of this initiative, the CIPimplemented Philippine project aims to improve urban food systems by strengthening enterprise capacities of informal vendors, thereby helping to improve food supply and diets of the urban populace and securing economic opportunities, especially for the urban poor. This initial study reports findings from an assessment of the participation of informal food vendors in the agrifood systems of two Metro Manila pilot cities in order to contribute to the design of capacity development interventions in the next phase. Findings show that informal food vendors play a significant role in food provisioning, livelihood and income generation across the food chain. They are found to be key links between multiple food production locations and consumers in primary, secondary, and satellite markets, especially benefiting the urban poor. Recognizing these, city governments started policy initiatives to improve the functioning of informal vendors in market spaces, coming up with options that address issues on relocation, regularization, and marketing. At this point, though, it is still largely a work in progress. Evidence suggests a greater likelihood of informal food vendors contributing to resilient cities by strengthening their enterprise skills and giving them access to information, innovation, and support services to improve selling practices, sanitation and hygiene, and make nutrient-sensitive food chain improvements. Based on these, it is proposed that designs for developing the capacity of this sector involve the adaptation of the CIP-developed Farmer Business School into the Vendor Business School, integrating the capacity and learning needs of informal vendors in partnership with city governments and stakeholders.